MARKET STRUCTURE AND BANK COMPETITION CONDITIONS IN MALAYSIA - Abd. Kadir, Hazlina; Habibullah, Muzafar Shah; Law, Siong Hook; Mohamed, Azali (Journal of Technology Management and Business, 2014)
This study investigates the market structure of banking industry in Malaysia from 1996â€“2009, using the k-bank concentration ratio (CRk) and the Herï¬ndahl Hirschman Index (HHI). It also evaluates the monopoly of banks over the fourteen yearsâ€™ period using the â€˜H-statisticâ€™, Panzar-Rosse approach. The k-concentration ratio showed Malaysia was moderately concentrated market, moving to a less concentrated one. Meanwhile, the Herfindahl Hirschman Index result showed a constant concentration ratio throughout the period. The Panzar-Rosse H-statistics suggested that banks in Malaysia were operating under monopolistic competition based on total interest income and total revenue as the dependent variables. In the long-run equilibrium, the Panzar-Rosse H-statistics suggested that Malaysian banks were operating under perfect competition. The findings of this study highlight the importance of size, efficient risk management and liquidity in sustaining long run revenue and competition. In order to compete in the next era of globalization, an ongoing investment in technological aspects related to banking products and services should be one of the essential policies for the banks to prosper